Extracting Prototypical Facial Images from Exemplars. (November 2013) - Benson, Philip J; Perrett, David I
A computer graphic method for extracting a natural image of an individual's facial prototype, or average appearance, from a number of different images of that individual is presented. The process improves upon previous photographic and computational techniques. Synthesis of a person's average expression and pose from a sample of images is derived in an automatic and quantitative way. Possible uses of composite faces produced in this manner in psychological investigations of facial qualities (eg attractiveness) and in applied areas such as telecommunication are pointed out.